AN IMPROVED TECHNIQUE FOR THE BATCH PROCESSING OF SMALL WHOLEWOOD SAMPLES TO α-CELLULOSE - Loader N.J.; Robertson I.; Barker A.C.; Switsur V.R.; Waterhouse J.S. (My University, 1997)
We present details of a modified technique for the extraction of α-cellulose from wood samples. The revised technique, based upon the sodium chlorite oxidation method of Green (1963) utilises an ultrasonic bath and small Soxhlet thimbles to prepare α-cellulose from slivers of wholewood. These modifications facilitate the rapid batch processing of small wholewood samples to α-cellulose and yield a material with sufficient homogeneity as required for palaeoclimatic reconstruction.
Keywords: α-CELLULOSE; STABLE CARBON ISOTOPES; PALAEOCLIMATE RECONSTRUCTION; SOXHLET THIMBLE